ATP-controlled remodeling in reconstituted actomyosin - Sami C. Al-Izzi; Sedigheh Ghanbarzadeh Nodehi; Darius V. Köster; Richard G. Morris (Physical Review Research, 2025)
The cytoskeletal component actomyosin is a canonical example of active matter since the power-stroke cycle locally converts chemical energy in the form of adenoside triphosphate (ATP) into mechanical work for remodeling. Observing myosin II minifilaments as they remodel actin in vitro, we now report that at high concentrations of ATP, myosin minifilaments form metastable swirling patterns that are characterized by recurrent vortex and spiral-like motifs, whereas at low concentrations of ATP, such structures give way to asterlike patterns. To explain this, we construct the (quasi)steady states of a polar active hydrodynamic theory of actomyosin whose ATP-scaling is obtained from a microscopic, stochastic description for the ATP-dependent binding of the heads of single myosin II minifilaments. The latter codifies the heuristic that, since the power-stroke cycle involves the unbinding of myosin II heads from actin, increases in the concentration of ATP reduce the likelihood that a given myosin II minifilament has more than one head bound simultaneously, reducing its ability to generate contractile forces and increasing the relative likelihood of processive motion. This reproduces several qualitative and some quantitative aspects of experiments, providing evidence for the central phenomenon of the theory: an ATP-dependent active contractile instability. ATP therefore controls not only the rate at which work is done—i.e., the power—but also the mode by which this occurs.